Implementing Accessibility Principles in Alternative Dispute Resolution for Sharia Economic Disputes in Indonesia - Nurhani Fithriah; Dimas Dwi Arso; Arini Azka Muthia (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
The growth of Sharia-based businesses in Indonesia has prompted both bank and non-bank financing institutions to adhere to Sharia principles, establishing a framework of rights and obligations with consumers. Imbalances in this relationship occasionally result in defaults, leading to dispute resolution through litigation and alternative methods. This research, utilizing a normative approach, specifically delves into the accessibility principle within alternative dispute resolution (ADR) for Sharia economic disputes in Indonesia. Accessibility, a pivotal ADR tenet, is examined in the context of Basyarnas (National Sharia Arbitration Board), where its effectiveness relies on information and understanding levels between consumers and Sharia financial institutions. Basyarnas-MUI emerges as a potential community choice for Sharia dispute resolution, with envisioned enhanced accessibility through regional representative offices. Conversely, challenges in accessibility are noted in APS Institutions under OJK auspices, impeding public participation. Mandatory mediation in disputes adjudicated by religious courts offers an accessible avenue for dispute resolution. However, persistent obstacles exist in implementing the accessibility principle for alternative Sharia economic dispute resolution in Indonesia, particularly concerning constraints on out-of-court dispute resolution governed by standard contracts for economic activities